Improving higher education teaching with feedback of eye tracking glasses: An international and interdisciplinary study - Faiella, Filomena; Albano, Giuseppina; Attolino, Paola; Castaldi, Maria Chiara; Giordano, Marco; Lombardi, Maria Grazia; Mannese, Emiliana; Mascolo, Valentina; Ricciardi, Maria; Savarese, Giulia (Education Sciences & Society - Open Access, 2023)
The paper describes the purpose and the methods of the international project “Teaching in Higher Education Effectively via Eye-tracking” (THEE) and summarizes its findings. The project studied the eye movements of higher education teachers and students to reflect on how to improve the teaching-learning process. The participants were four professors and twelve students who wore eye tracking glasses during the lessons. The results of the study demonstrate a clear benefit of the approach based on collecting eye tracking data and teachers’ self-reflection on their own classroom practice. Concerning the analysis of gaze location and teachers and students’ behaviour, we noticed that the teachers looked mostly at the centre of the classroom and that the duration of the fixations depends on the size of the classroom and the type of subjects. Moreover, the teachers of scientific subjects seem to change their fixation duration distribution over the lessons analysed while the humanities lecturers appeared more static. The analyses also highlighted that the teachers of humanities subjects were found to be very focused on the cognitive processes, while teachers of scientific subjects were attentive to the way they can involve students in learning. On the other hand, students of the humanities mainly highlighted some operational factors related to the teacher’s lesson and to their own subsequent study, whereas students of scientific subjects seemed to show more attention to the factors related to the lesson and to activities carried out in the classroom.